Semiotic Analysis of Editorial Cartoons of the Philippine Artisan - Genesis Joy Arañas; Arlene Gorpido; Jewel Chrizelle Huraño; Louise Lane Icaro; Vyneth Jana Luna; Stephan Jenkins Norada; Jertrude Ellice Mendoza; Jellan Peñaredondo; Marie Jo Tess Ragos; Mark David Ramos; Cynic Tenedero (Advanced Qualitative Research, 2024)
The editorial cartoons of the Philippine Artisan played an imperative role in identifying and stimulating the public’s feelings toward current events. This study analyzes the signs and symbols used in the chosen fifteen (15) editorial cartoons of Philippine Artisan, the official student gazette of the Technological University of the Philippines, in expressing relevant social issues. This is a qualitative study anchored by a descriptive research design. Semiotic analysis was used to examine symbols, signs, and meanings within the chosen cartoons to achieve a comprehensive analysis. It was found that most of the common themes covered by the editorial cartoons were power abuse, corruption, incompetent leaders, a disorganized capitalist system, government inaction, careless solutions, and school-related problems. The publication still provided an impact by educating students about the current issues and opening their minds to what we are currently facing within the university and society. This also concludes that the cartoonists have clearly communicated their messages and their criticism of the current leadership and the call for action.